Martyrs' day commemoration. - Gadar Memorial Steering Committee; Punjabi People's Cultural Association; South Asians for Collective Action:::Creator::::::::::::
Program flier of Martyrs' Day Commemoration at Gadar Memorial Hall. Program consists of introduction on Gadar martyrs, film on Shankar Guha Niyogi, talk with slide presentation on recent social movements in India, and poetry reading.